THEORETICAL FRAMEWORK OF ISLAMIC WORK ETHICS AS A MEDIUM OF DA’WAH IN BUSINESS ENVIRONMENT - Shakir Husein Kalid; Mohd Rushdan Mohd Jailani (Journal of Islamic, Social, Economics and Development, 2019)
Lacking of good values among staffs in any organizational always lead to maliciouscases such as cheating or scam, contract dispute, bankruptcy, bad debts, fraud of documents,bribery and others. These happened due to the separation between good values and businessenvironment which has a negative impact not only to industry but also on human lives. It is verytimely to curb these problems by introducing a practical solution. Therefore this paper is aimedto elaborate the relationship between Islamic work values, Islamic work ethic and Islamic workculture. For this purpose, this paper will take the principles of Islamic Working Ethics (IWE)that had been implemented in business environment of Small Medium Enterprises (SME) inSelangor. It is important for SME industry to have positive management style and businessethics that can be linked to the religion and Ibadah. This paper will also share the theoreticalframework of IWE as a means of Da’wah in business environment by using the pillars whichare Piety (Taqwa) and Moral (Akhlak) as a foundation of IWE. In addition to that this paperwill highlight how IWEs is so influential in business environment that bring positive impacts tothe business growth